Connect with a community that values knowledge and expertise on IDNLearn.com. Our platform is designed to provide reliable and thorough answers to all your questions, no matter the topic.

solve for s. -6 = s - 9​

Sagot :

S=3
-6=s-9
+6 +6 add six to both sides
0=s-3
-s -s Subtract s on both sides
-s=-3
Divide by -1 to get positive
s=3

Answer:

s = 3

Step-by-step explanation:

-6 = s - 9

Seap sides and so that all variable terms are on the left hand side.

s - 9 = -6

Add 9 to both sides.

s = -6 + 9

Add -6 and 9 to get 3.

s = 3

Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. Thank you for choosing IDNLearn.com for your queries. We’re here to provide accurate answers, so visit us again soon.